(3dH GddHGH aj JMQjQ GdCfSGHs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3GHf GdGKjQ , YR GdOjf CHh GdMSf,J (B630 (3g` s ((3YHOGdcQje Hf CHj LGeY GdLHQJi s)
(3ChdgG (B:s
(3GdMeO ddg GdeJfRg Yf GdCTHGg hGdEfSGf gPG eG GTJO Edjg MGLI s
(3BNQgG (B:s
(3GNJUQ ai YTQI CjGe eJhGdjI BNQgG s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B228s
Keywords: (3GdJGQjNs